The FH phenotype: monogenic familial hypercholesterolaemia, polygenic dyslipidaemia and other causes - Mariano, C. (2018)
Familial hypercholesterolaemia (FH) is a monogenic autosomal condition where patients present very high LDL-C values and an increase cardiovascular risk. FH is caused by mutations in 3 genes: LDLR, APOB and PCSK9. However in only about 40%-50% of the cases an FH causing mutation is found. The FH phenotype has been associated recently to other monogenic disorders as lysosomal acid lipase deficiency or can have a polygenic origin. The aim of this work was to characterize the origin of FH phenotype in a cohort of patients with a clinical diagnosis of FH.